Herd recording in New Zealand : being a dissertation presented in partial fulfilment of the requirements for the degree of M. Agr. Sc., Massey Agricultural College, University of New Zealand - Edey, T N (Massey University, 1952)
Recent developments have made herd recording in New Zealand the responsibility of a single organisation, the New Zealand Dairy Board, and since August 1st, 1951, there has been virtually only one system of recording. However, since 1904, when the Department of Agriculture introduced systematic testing in the Weraroa herd, many organisations and numerous systems of recording have contributed to the development of the herd recording movement. The time is opportune, therefore, for a study of this work in New Zealand, embracing the history of production recording, a review of the associated investigational work, and an assessment of the past role and probable future place of herd recording in the improvement of dairy cow production. To supplement data from published material much information has been obtained from private files and personal interviews. In this respect, grateful acknowledgement is due particularly to Professor W. Riddet for access to his private files relating to herd recording, and for helpful discussion. Thanks are due to the Director and staff of the Herd Recording Department of the New Zealand Dairy Board for their assistance: to Mr. H. G. Philpott, late of the Dairy Division, Department of Agriculture; to Mr. C. M. Hume; to my supervisor, Dr. A. Stewart for helpful guidance and criticism; and to many others for their ready co-operation. This work was completed during the tenure of a Victorian Government Scholarship.
Keywords: Cattle; Pedigrees; Dairy cattle; Testing